Red Algae in the Genomic Age - Seckbach, Joseph.; Chapman, David J. (Cellular Origin, Life in Extreme Habitats and Astrobiology,, 2010)
This volume covers the modern biology and the speciation of the red algae (Rhodophyta) from unicellular Cyanidia up to macrocellular sea weeds. A team of peer reviewers has reviewed all chapters. The chapters describe a range of topics from cave algae from Atacama, Chile, to genomes of red algae. Some chapters deal with the carbohydrates, physiological mechanisms, and realtionship between red algae and neurodegenerative disease. Other chapters deal with organellar - nuclear genes and taxonomic revision. Emphasis is placed upon the rhodophytan chloroplast, its origin, evolution, division machinery and pigmentation. The reader will find in this book lots of new information on the red algae.